LIGAND-BASED ANALYSIS OF COMPOUNDS ON GARLIC USING SWISS SIMILARITY - Reynaldi, Muhammad Andre (Journal Pharmacy Of Tanjungpura, 2025)
Garlic (Allium sativum) is widely recognized for its bioactive compounds with potential therapeutic effects. This study aimed to conduct a ligand-based analysis of active garlic compounds using SwissSimilarity to identify structural similarities with known bioactive molecules. The compounds analyzed included allicin, alliin, and diallyl sulfide. Molecular structures were obtained from the PubChem database and analyzed through SwissSimilarity by selecting the "Bioactive molecules" class and applying the "Combine LigandExpo" screening method. The results showed that allicin exhibited a high similarity score (0.845) with 3-(prop-2-ene-1-sulfinyl)-propene-1-thiol, known as a glutathione reductase inhibitor, as well as other structures related to antibacterial and antioxidant activities. Alliin demonstrated a high similarity to S-acetonylcysteine (0.992) and cysteine-S-acetamide, suggesting potential antiviral and immunomodulatory properties through interactions with human and viral proteins. Diallyl sulfide showed similarity with tetramethylthiuram monosulfide (0.701) and amyl nitrite, indicating possible effects on the cardiovascular system. This study confirms that a ligand-based computational approach can effectively identify the pharmacological potential of garlic compounds and provides a scientific basis for further development of natural product-based drug candidates.